Asthma, Anxiety and Depression are they walking together? Cross- Sectional Descriptive Study - Xavier Flor-Escriche; Roser Poblet- Cortés; Laia Lamarca-Fornell; Judit Mendez-Gomez; Sílvia Álvarez- Álvarez; Sara-Anna; MVictoria Feijoo-Rodriguez (Archives of Pulmonology and Respiratory Care - Peertechz Publications, 2016)
Background/Objectives: The association between asthma and mental health disorders is well known, both anxiety and depression being the most common ones. The aim is to determine the proportion of anxiety and/or depression in an asthmatic population compared to a non-asthmaticone in a Primary Care centre. Secondary objectives: Assess the association between the severity of asthma and its level of control and anxiety and/or depression. Methods: Cross-sectional descriptive study, 317 patients diagnosed of asthma and 306 without asthma, aged between 17 to 70 years old, recruited from a primary care centre. Goldberg test was performed to detect anxiety and/or depression. Other variables analysed were: age, sex, previous diagnosis of anxiety and/or depression, associated chronic diseases, type of asthma and degree of its control. Results: 70% of the people in the asthmatic group were women and 52% in the non-asthmatic group. The mean age was of 43 (SD 16.89) and 48 (SD 14.09) years old, respectively 57.1% had intermittent asthma. 62.7% of asthmatics had good control. Goldberg test in the group of asthmatic patients showed 51.1% (p = 0.0001) of anxiety and 57.4% (p = 0.0001) of depression. The results were adjusted for age and sex maintaining the association between asthma and anxiety with an OR = 1.8 (95% CI: 1.3-2.6) and depression OR = 2.1 (95% CI: 1.5 to 3.0). Patients with a higher level of asthma control had less anxiety (p = 0.002) and depression (p = 0.004). Conclusions: Asthmatic patients had more anxiety and depression. Higher asthma control was associated with less anxiety and depression.